Maxim Observance and Non-Observance on Meilin’s Utterances in Turning Red Movie - Pramita, Cheryl Firdausi; Pradipta , Bramantya (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study explores the observance and non-observance of Grice’s Cooperative Principle in the speech of Meilin Lee, the main character in Pixar’s animated film Turning Red. Focusing on her dialogues with both family members and friends, this research aims to identify how Meilin observes, flouts, or violates the conversational maxims of Quantity, Quality, Relevance, and Manner. Using a qualitative descriptive approach, the study analyzes 97 utterances selected from the film’s transcript. The results show that the maxim of relevance is most frequently used in family interactions, often flouted to avoid confrontation or express resistance. Meanwhile, the maxim of quantity dominates Meilin’s interactions with her friends, frequently flouted for humor or expressive emphasis. Violations are more common in family settings, reflecting emotional concealment or tension, whereas flouting is more prevalent in casual, peer-based conversations. These findings highlight how characters’ maxim use shifts depending on relational context and suggest that non-observance strategies serve functions such as avoidance, emphasis, emotional control, or indirect expression. The study contributes to pragmatic analysis in fictional discourse and offers insight into how animated characters reflect real-world communication dynamics Keywords: Cooperative Principle, Gricean Maxim, Pragmatic, Turning Red.